2018
DOI: 10.3390/ijms19071914
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Subcellular Phosphate Transport Machinery in Plants

Abstract: Phosphorus (P) is an essential element required for incorporation into several biomolecules and for various biological functions; it is, therefore, vital for optimal growth and development of plants. The extensive research on identifying the processes underlying the uptake, transport, and homeostasis of phosphate (Pi) in various plant organs yielded valuable information. The transport of Pi occurs from the soil into root epidermal cells, followed by loading into the root xylem vessels for distribution into oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 81 publications
(143 reference statements)
2
27
0
Order By: Relevance
“…This phenomenon might be attributable to the competition between P and Se during plant transport, and as P is an important macronutrient for plants, it might be transported preferentially, especially under P-deficient condition. Previous studies have shown that OsPT6 likely mediates P translocation throughout the plants and is strongly up-regulated under P starvation (Luan et al, 2017;Srivastava et al, 2018). The transcript abundance of OsPT6 was notably elevated in the roots of an ltn1 mutant, which exhibited much higher rates of Se uptake than wide-type plants (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This phenomenon might be attributable to the competition between P and Se during plant transport, and as P is an important macronutrient for plants, it might be transported preferentially, especially under P-deficient condition. Previous studies have shown that OsPT6 likely mediates P translocation throughout the plants and is strongly up-regulated under P starvation (Luan et al, 2017;Srivastava et al, 2018). The transcript abundance of OsPT6 was notably elevated in the roots of an ltn1 mutant, which exhibited much higher rates of Se uptake than wide-type plants (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 87%
“…In recent decades, numerous studies have investigated the subcellular distributions of various heavy metals (such as cadmium and lead) to reveal the tolerance and detoxification strategies of plants (Sha et al, 2019;Xiao et al, 2019;Yang et al, 2019). Other studies also focused on nutrient elements (Grillet et al, 2014;Srivastava et al, 2018) and rareearth elements (Shen et al, 2014). Nonetheless, a few studies have reported about the subcellular Se distribution and accumulation in plants.…”
Section: Introductionmentioning
confidence: 99%
“…Up‐regulated expression of these PHT1 genes might contribute to increased Pi uptake from the soil by the roots and improved root‐to‐shoot translocation of Pi in chickpea, as reported for Arabidopsis plants (Lapis‐Gaza, Jost, & Finnegan, 2014; Mudge, Rae, Diatloff, & Smith, 2002). With respect to leaves, three PHT1 genes ( PHT1;3 / XM_004495263.2 , PHT1;4 / XM_012713920.1 and PHT1;9 / XM_004505264.2 ) were up‐regulated in response to Pi deficiency (Table 1 and Figure S6), which might contribute to increased Pi remobilization from source leaves to sink leaves of –Pi/+NO 3 − plants (Chang et al, 2019; Srivastava et al, 2018). In addition, while the expression of genes belonging to the PHOSPHATE1 ( PHO1 ) family, which are implicated in the loading of Pi into the xylem and Pi translocation from roots to shoots (Srivastava et al, 2018), was not altered in the roots under Pi starvation, up‐regulation of the PHO1;H1 / XM_004509529.2 gene was observed in the leaves of –Pi/+NO 3 − versus +Pi/+NO 3 − plants (Table 1 and Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Phosphorus (P) is a macronutrient essential for cellular processes such as energy production, redox reactions, photosynthesis, and phosphorylation/dephosphorylation reactions [146]. Phosphorus enters the plant root system in the form of inorganic P (Pi), such as PO 4 3− , H 2 PO 4 − , or HPO 4 2− , through an energized process involving H + /Pi co-transport in order to overcome the negative membrane potential [146].…”
Section: Molecular Actors Involved In Lateral Transport Of Solutesmentioning
confidence: 99%
“…Phosphorus (P) is a macronutrient essential for cellular processes such as energy production, redox reactions, photosynthesis, and phosphorylation/dephosphorylation reactions [146]. Phosphorus enters the plant root system in the form of inorganic P (Pi), such as PO 4 3− , H 2 PO 4 − , or HPO 4 2− , through an energized process involving H + /Pi co-transport in order to overcome the negative membrane potential [146]. Pi is then transported through the different root tissues through the action of, at least, the AtPHO1 and AtPHO1;H1 transporters, which are expressed in the endodermis and the pericycle, respectively, before being loaded into the xylem sap for root-to-shoot transport [102,103].…”
Section: Molecular Actors Involved In Lateral Transport Of Solutesmentioning
confidence: 99%